Reintrepretasi Senif Riqab Sebagai Mustahik Zakat Menurut Perspektif Ulama Kontemporer (Studi Pemikiran Sayyid Muhammad Rasyid Ridha) - T. Habibie; Fazil; Zulaiva Ulya (Journal of Contemporary Indonesian Islam, 2026)
In the distribution of zakat, Al-Ashnaf Al-Samaniyah are those people who are entitled to receive zakat and riqab is one of them. In this modern life, it is no longer possible to find a riqab or a slave. Then the distribution of zakat to riqab is questionable. In an attempt to reinterpret the meaning of riqab with current conditions, Sayyid Muhammad Rasyid Ridha offered a thought on the reinterpretation of riqab. Among them are: First, how is the concept of riqab as mustahik zakat according to Sayyid Muhammad Rasyid Ridha's view. Second, how is ijtihad method used by Sayyid Muhammad Rasyid Ridha in interpreting riqab as mustahik zakat today. Third, how is the relevance of Sayyid Muhammad Rasyid Ridha's thoughts about riqab as Mustahik zakat to the present. This research used a qualitative method with a descriptive approach to the method of collecting through documentation in the form of data, books, journals, theses and other articles relating to the object of research. The results of this research explain that: The concept of mustahik riqab according to Sayyid Muhammad Rasyid Ridha is: to release Muslim prisoners who were held captive by enemies, to release someone from undue accusations, to help maids who were held captive and tortured by their employers and to release Muslim nations who were colonized by kafir. Nowadays, the meaning of riqab needs to be expanded to the benefit that will arise from it. The method used by Sayyid Muhammad Rashid Ridha is ijtihad Intiqa'i method. So that the relevance in redefining riqab is hoped that there will be a development that is closer to other meanings that do not come out of the basic concept of riqab itself, so it is necessary to find solutions for the distribution of zakat in this era.